Dokumen Bisnis Sosial yang Efektif Dalam Komunikasi Organisasi - Ardhia Meianti; , Fitri Rorizki; Suhairi Suhairi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2021)
Information is one of the key sources of organizational value. As information carriers, documents, in some form, store the majority of business information. With the widespread introduction of social software in companies, much information is now created in social applications; leading social content to become one of the fastest growing content types. As with other content types, social content must be managed in order to realize its value and to minimize information risks. However, there is a lack of understanding about what social documents really are, what distinguishes them, and how they should be differentiated from other social content. Therefore this study examines social business documents by differentiating between social content and social documents and analyzes the characteristics of social documents. From this a working definition of social business documents is developed and challenges for their management are outlined.